Regulation of Dynamin Oligomerization in Cells: The Role of Dynamin–Actin Interactions and Its GTPase Activity. (24th June 2014) - Gu, Changkyu; Chang, Joann; Shchedrina, Valentina A.; Pham, Vincent A.; Hartwig, John H.; Suphamungmee, Worawit; Lehman, William; Hyman, Bradley T.; Bacskai, Brian J.; Sever, Sanja
Abstract Dynamin is a 96‐kDa protein that has multiple oligomerization states that influence its GTPase activity. A number of different dynamin effectors, including lipids, actin filaments, and SH3‐domain‐containing proteins, have been implicated in the regulation of dynamin oligomerization, though their roles in influencing dynamin oligomerization have been studied predominantly in vitro using recombinant proteins. Here, we identify higher order dynamin oligomers such as rings and helices in vitro and in live cells using fluorescence lifetime imaging microscopy (FLIM). FLIM detected GTP‐ and actin‐dependent dynamin oligomerization at distinct cellular sites, including the cell membrane and transition zones where cortical actin transitions into stress fibers. Our study identifies a major role for direct dynamin–actin interactions and dynamin's GTPase activity in the regulation of dynamin oligomerization in cells. <inline-graphic xlink:href="ark:/27927/pghtb26kcs" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />